Phytochemical composition and antioxidant activities of leaf extracts of Viola odorata from Kishtwar, Jammu and Kashmir. Issue 1 (2nd January 2020) - Aslam, Lubna; Kaur, Ramanjeet; Kapoor, Nisha; Mahajan, Ritu
ABSTRACT: Phytochemical composition and in vitro antioxidant activity of solvent extracts of Viola odorata leaves were investigated. High-performance liquid chromatography (HPLC) profile of stigmasterol in V. odorata leaves was examined. The extracts tested positive for the presence of alkaloids, flavonoids, terpenoids, saponins, and phenolics, which were present in high quantity in ethanol extract. Greatest radical scavenging activity (EC50 160 µg mL −1 ) and ferric reducing potential (16.9 equivalent µmol of Fe 2+/ g sample) was observed in ethanol extract. Thin-layer chromatography (TLC) fingerprinting confirmed the presence of stigmasterol in all the extracts as evidenced by their Rf values which was similar to that of standard (0.9). HPLC profiling of ethanol extract revealed the presence of 0.002 µg mL −1 stigmasterol in the leaves.